2012
DOI: 10.1136/injuryprev-2012-040590q.1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of intimate partner violence among male military personnel and civil servants in Ibadan, Nigeria: a comparative study

Abstract: Background The nature of training and work of the military personnel and civil servants may affect their relationships with their intimate partners in different ways. Objectives The objective of this study was to assess and compare the prevalence and correlates of intimate partner violence (IPV) against female partners among male military personnel and civil servants in Ibadan, South-western Nigeria. Methods A cross sectional study was carried out using a multi-stage sampling technique. A self administered que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 16 publications
(25 reference statements)
1
13
1
Order By: Relevance
“…This is higher than previous reports from Malawi (13%-20%) [36], Kenya (37%) [18], South Africa (>20%) [1], and Uganda (36.6%) [37]. However, a Nigerian subnational study among civil servants found a far higher prevalence during the last 12 months (66%) [38]. The large cross-country differences may be explained by the contextual sociocultural factors and by methodological heterogeneity.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…This is higher than previous reports from Malawi (13%-20%) [36], Kenya (37%) [18], South Africa (>20%) [1], and Uganda (36.6%) [37]. However, a Nigerian subnational study among civil servants found a far higher prevalence during the last 12 months (66%) [38]. The large cross-country differences may be explained by the contextual sociocultural factors and by methodological heterogeneity.…”
Section: Discussioncontrasting
confidence: 55%
“…IPV is generally defined as a multifaceted issue with diverse aetiological factors and embedded predominantly into the sociocultural value system determining women's susceptibility to violence and aggression. Sociocultural factors are by far the most commonly cited issues associated with higher degrees of exposure to IPV [17,26,38]. A review of the current literature suggests that the central mechanism through which these factors affect IPV is their impact on women's socioeconomic empowerment.…”
Section: Discussionmentioning
confidence: 99%
“…A recent global IPV prevalence estimate reveals that one in three women across the world has experienced at least one form of IPV (WHO, 2017). Similarly, it has been well documented that there is high prevalence of IPV against women in Nigeria ( Adegbite & Ajuwon, 2015;Adejimi, Fawole, Sekoni, & Kyriacou, 2014;Aduloju, Olagbuji, Olofinbiyi, & Awoleke, 2015;Antai, 2011;Balogun, Owoaje, & Fawole, 2012;Ezebuka, Sam-Agudu, Erekaha, & Dairo, 2015;Kunnuji, 2015). According to the Nigerian Demographic Health Survey (NDHS) of 2008, about 18% of married Nigerian women reported having experienced physical or sexual IPV from their husband (National Population Commission [NPC] and Inner City Fund [ICF] Macro, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Physical or sexual IPV is known to affect more than one-third of all women globally, with the African average being slightly higher at 36.6%, as estimated by the World Health Organization [23]. The prevalence varies widely across countries in several parts of Africa: Malawi (13-20%) [16], Kenya (37%) [24], South Africa (>20%) [5], Zimbabwe (63.1%, among pregnant women) [25] and Nigeria (66%) [26]. A meta-analytical report found that in 2010 the lifetime prevalence of physical and sexual IPV was 30.0%, with the prevalence being highest (65.64%) for central sub-Saharan Africa [27].…”
Section: Discussionmentioning
confidence: 99%
“…Data for this study were based on the women's questionnaire. More detailed version of the sampling techniques regarding the surveys was published in the final reports (24)(25)(26)(27) [19].…”
Section: Data Sourcementioning
confidence: 99%